2018
DOI: 10.1111/pace.13540
|View full text |Cite
|
Sign up to set email alerts
|

Successful cryoablation of atrial fibrillation from jugular approach in patient with interrupted inferior vena cava and azygos continuation

Abstract: We herein report successful cryoablation of paroxysmal atrial fibrillation via right jugular vein in a patient with interrupted inferior vena cava. We preferred cryoablation instead of radiofrequency ablation in the treatment of our patient. For stronger support in aiming the Brockenbrough needle toward the septum, we manuallly curved the needle with a 120 • angle about 6 cm proximal to the tip. After successful transseptal puncture, we performed balloon dilatation in the septal puncture zone to facilitate pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A small number of other cases in the literature with a similar superior approach for AF ablation have shown this approach to be feasible, when necessary. [1][2][3][4][5]8 The IVC is formed from anastomosis of 3 pairs of veins during the fifth to seventh weeks of gestation, with 5 segments contributing to its final structure. 6 Interruption or stenosis of this structure has been found in ,1% of cases in imaging series, and is asymptomatic in cases where the azygos system is well developed, which occurs in roughly half of these.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small number of other cases in the literature with a similar superior approach for AF ablation have shown this approach to be feasible, when necessary. [1][2][3][4][5]8 The IVC is formed from anastomosis of 3 pairs of veins during the fifth to seventh weeks of gestation, with 5 segments contributing to its final structure. 6 Interruption or stenosis of this structure has been found in ,1% of cases in imaging series, and is asymptomatic in cases where the azygos system is well developed, which occurs in roughly half of these.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vein isolation to treat atrial fibrillation (AF) is challenging where the usual femoral route is not possible. [1][2][3][4][5] Interruption of the inferior vena cava (IVC) is a rare anatomic variant, with or without azygos venous system drainage of the lower body into the superior vena cava (SVC). 6,7 This anatomy necessitates an alternative approach for transseptal puncture to allow catheter access to the left atrium, and has been described for both radiofrequency and cryoballoon ablation strategies for AF ablation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reports described manual modifications to the standard transseptal equipment to achieve access. For example, the Brockenbrough needle was often manually bent to 120–150° to provide greater reach and similar angle of entry across the inter‐atrial septum (IAS) 15,17–21 …”
Section: Approaches To Ablation Of Specific Arrhythmiasmentioning
confidence: 99%
“…IVC hypoplasia, an alternative technique and vascular access are required. It has been reported that trans-jugular vein access is feasible for catheter ablation of AF, with both technology (cryoballoon and radiofrequency) [2][3][4][5][6] . We report successful cryoablation of paroxysmal AF via RIJV in a patient with hypoplasia of IVC.…”
Section: Introductionmentioning
confidence: 99%